Cardiovascular Biomarker Profile on Antiretroviral Therapy Is Not Influenced by History of an IRIS Event in People With HIV and Suppressed Viremia. (11th January 2020) - Gouel-Cheron, Aurelie; Nason, Martha; Rupert, Adam; Sheikh, Virginia; Robby, Greg; Fahle, Gary A; Sereti, Irini
Abstract: Immune reconstitution inflammatory syndrome (IRIS) is characterized by release of proinflammatory cytokines and tissue inflammation occurring early after antiretroviral therapy (ART) initiation. The role of previous IRIS events in persistent chronic inflammation in people with HIV is currently unclear. In this retrospective analysis of 143 participants who maintained suppression of HIV viremia, we compared biomarkers related to inflammation, coagulation, and cardiovascular risk after 3 years on ART in participants with and without a history of IRIS. There was no evidence of higher levels of persistent chronic inflammation in people with HIV who had a history of an IRIS event. ClinicalTrials.gov Identifier . NCT00286767. Abstract : In a cohort of people with HIV on antiretroviral therapy (ART), previous history of immune reconstitution inflammatory syndrome upon ART initiation did not affect measured levels of biomarkers associated with inflammation, coagulation and cardiovascular risk after 3 years of ART.